Quantitative assessment of microplastic in sandy beaches of Gujarat state, India. (August 2022) - Rabari, Vasantkumar; Patel, Krupal; Patel, Heris; Trivedi, Jigneshkumar
Abstract: The present study was carried out to quantify microplastic prevalence among 20 sandy beaches on the Gujarat coast. Beaches were categorised into three different classes, viz. low-impacted sites, moderately impacted sites, and highly impacted sites based on anthropogenic pressure. Microplastic (MP) (≤ 5 mm) contamination on the beaches varied with an average of 1.4 MPs/kg to 26 MPs/kg sediment. Sutrapada site-1 and Porbandar showed the highest and lowest mean abundance of microplastics, respectively, among 20 selected beaches. Out of the total assessed microplastics, threads were the maximum (89.98%), followed by the films (4.75%), fragments (3.36%) and foam (1.89%). In terms of colour and size, different microplastics were recorded in this study. The chemical composition of microplastics was identified by ATR-FTIR as polypropylene (47.5%), polyethylene (26%), and polystyrene (25%). Tourism and fishing activities are the possible sources of higher microplastic contamination at highly impacted sites. Highlights: Microplastic pollution has been reported in sediments of 20 sandy beaches of Gujarat, India. A total of 1158 microplastics of mainly three types were detected. Mean abundance of microplastics ranged from 1.4 to 26 MPs/kg. Chemical nature of MPs was identified as polypropylene, polyethylene and polystyrene. Fisheries and tourism were the main causes of MPs prevalence on Gujarat coast.